(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
Research to carry out supervision of teachers, school principals and supervisors in the education office using local wisdom values. The specific goal to be achieved is the formation of an academic supervision model based on Hibualamo cultural values, which is a value system that is highly upheld by the people of North Halmahera. The research methods used are qualitative and quantitative, while data analysis is descriptive qualitative and descriptive quantitative. The data collection technique involves assessing documents and asking for expert opinions on their validity. The techniques used in this development stage are quantitative and qualitative descriptive; while the model findings are hypothetical models. The results of developing an academic supervision model based on Hibualamo cultural values include the management functions of planning, organising, implementing and reporting. The academic supervision model based on Hibualamo cultural values is effective in improving the performance of teachers in North Halmahera in aspects of learning planning, implementation and assessment aspects.